Social entrepreneurship and business ethics understanding the contribution and normative ambivalence of purpose-driven venturing - Zeyen, Anica; Beckmann, Markus (Routledge, 2019)
Social entrepreneurs are change makers that aim to solve society's unsolved problems. Not surprisingly, social entrepreneurship has thus created high expectations. To better understand the potential as well as the limitations of social entrepreneurship, however, a more nuanced approach is needed in two ways. First, social entrepreneurship is a multi-level phenomenon. It spans macro-level questions as well as meso-level questions and, finally, micro-level questions. If we really want to understand social entrepreneurship, we need to bring together all three levels of analysis and see how they are connected. Second, while social entrepreneurship can certainly produce socially desirable outcomes, we also need a critical perspective to capture potential undesirable effects that social entrepreneurship can cause, often unintendedly, in society, in markets, in organizations, and for individuals. To this end, an ethical perspective can help complement the positive analysis of social entrepreneurship with a discussion of the normative implications of its potential "dark side". Looking at social entrepreneurship from both a multi-level analysis and an ethical perspective, Social Entrepreneurship and Business Ethics takes the reader on a journey through the "bright side" as well as the potential "dark side" of social entrepreneurship for societies, organizations, and individuals. Highlighting both, this book not only seeks to provoke researchers and students to advance their understanding of social entrepreneurship. It also hopes to help practitioners to better realize the positive contributions of social entrepreneurship for society
Keywords: Social entrepreneurship; Business ethics